Exploration of potential lipid biomarkers for premature canities by UPLC‐QTOF‐MS analyses of hair follicle roots. Issue 8 (17th August 2020) - Wang, Hecong; Wang, Jiateng; He, Congfen
Abstract: Background: The rate of premature greying, referred to as canities, varies among populations, and effective treatments are lacking. However, few studies at the molecular level have been reported. Objectives: Comparing lipid profiles of individuals with premature canities and healthy volunteers to explore the mechanism of premature canities. Methods: Ultra‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry (UPLC‐QTOF‐MS) was used to detect lipids in the hair follicle root. Multivariate data analysis was used to show lipid changes in follicle roots. Results: We identified lipids in the hair follicle root that differ between black and white hair and analysed key lipids contributing to white hair development. We divided the samples into three groups: PC‐WH (Premature canities‐White hair), PC‐PH (Premature canities‐Pigmented hair), Control‐PH (Pigmented hair). Phosphatidylethanolamine (PE), phosphatidylcholine (PC), vitamin D3 (VD3) and cholesterol in Control‐PH were higher than those in PC‐WH. Sphingomyelin (SP), phosphatidic acid (PA), VD3 and diglyceride (DG) were lower in PC‐WH than in PC‐PH. Levels of VD3 were highest in Control‐PH, gradually decreased as the severity of PC‐PH increased and were lowest in PC‐WH. Conclusion: There are 7 main class candidate compounds involved in the generation of white hair. VD3 showed a substantial decrease in white hair and was a potential target for further studies of premature canities.